2021
DOI: 10.1155/2021/5522788
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effect of Knowledge Network Embedding on the Dynamic Capabilities of Small and Micro Enterprises

Abstract: In the complex and dynamic economic environment, the growing pain of small and micro enterprises is long-standing. It is urgent to strengthen the research on the endogenous growth mechanism of small and micro enterprises. Based on the background of the era of knowledge-driven economy, this paper explores the relationship between knowledge network embeddedness and dynamic capabilities of small and micro enterprises with environmental munificence as the regulating variable. We have the structural equation empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…That is, higher relational embeddedness is not necessarily better (Burt, 1992 ; Uzzi, 1997 ; Obukhova and Zhang, 2017 ). This is inconsistent with Rodrigo-Alarcón et al ( 2018 ), Ai and Peng ( 2021 ), Zheng ( 2021 ), and Zhou et al ( 2021 ), who found that relational capital may positively predict dynamic capabilities. As mentioned earlier, most of the previous literature shows the positive effects of relational embeddedness.…”
Section: Discussionmentioning
confidence: 67%
“…That is, higher relational embeddedness is not necessarily better (Burt, 1992 ; Uzzi, 1997 ; Obukhova and Zhang, 2017 ). This is inconsistent with Rodrigo-Alarcón et al ( 2018 ), Ai and Peng ( 2021 ), Zheng ( 2021 ), and Zhou et al ( 2021 ), who found that relational capital may positively predict dynamic capabilities. As mentioned earlier, most of the previous literature shows the positive effects of relational embeddedness.…”
Section: Discussionmentioning
confidence: 67%
“…The findings imply that dynamic capabilities are crucial for firms seeking to excel in global product development. These capabilities encapsulate an organization's ability to sense, seize, and transform internal and external resources to effectively navigate changing environments [21,94], which is essential for firms to identify opportunities, mitigate threats, and adapt to dynamic market conditions. Moreover, the cognitive diversity among top executives can lead to variations in dynamic managerial capabilities, influencing organizational performance during periods of change [67,95].…”
Section: Discussionmentioning
confidence: 99%
“…(3)ThemoderatingroleofEM.EmpiricalevidenceshowsthatEMnegativelyregulatesthe relationshipsbetweentheKMCandtheQOofSMEsandthatbetweenKMCandORE.Althougha highlevelofEMprovidesarelaxedgrowthenvironmentforSMEs,theavailabilityofresourcescan easilybreedinertiaandweakenitsawarenessofendogenouscompetitivenessthroughknowledge management (Zheng, 2021). Policy dependence and tendencies that focus on the short-term can alsobringshort-termfluctuationsinoutput.However,theOREconstructionandQOarelong-term strategicbehaviors.Therefore,inanenvironmentwithlowmunificence,itwouldbemorehelpfulto strengthentheroleofknowledgeabsorptionandutilizationinOREandqualityimprovement.This mayexplainwhySMEsinresource-poorregionscanoutperformthoseinresource-richregionsin termsofcompetitivenessandlifeexpectancy.…”
Section: Discussionmentioning
confidence: 99%